2013
DOI: 10.1260/0263-6174.31.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Removal of As3+ Using Chitosan–Montmorillonite Composite: Sorptive Equilibrium and Kinetics

Abstract: In this study, the sorptive removal of As 3+ with promising sorption efficiency up to a very low concentration has been investigated using chitosan-montmorillonite (MMT) composites (in the form of powder and beads). In addition, the recovery of the composite from the sorbent is proposed as well. The sorbent has been observed to show a sorption efficiency of 42.0% from 0.006 µg ml -1 of metal ion. The batch adsorption model was developed to predict the equilibrium adsorption capacity with respect to the pH of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 20 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…They reported the removal of more than 84% for each element. The enhanced efficiency of chitosan/clay composites for other heavy metals removal such as arsenic, selenium, copper, and lead was also reported. Ali et al (2019) reported the preparation of phytic acid-doped polyaniline-MMT nanofibers for heavy metal adsorption.…”
Section: Introductionmentioning
confidence: 85%
“…They reported the removal of more than 84% for each element. The enhanced efficiency of chitosan/clay composites for other heavy metals removal such as arsenic, selenium, copper, and lead was also reported. Ali et al (2019) reported the preparation of phytic acid-doped polyaniline-MMT nanofibers for heavy metal adsorption.…”
Section: Introductionmentioning
confidence: 85%
“…Table 1 distinguishes various chitosan based biocomposites based on different solvent systems. Chitosan-montmorrilonite [9][10][11][12][13][14][15], Chitosan-activated clay [16], Chitosan-oil palm ash [17], Crosslinked chitosan-coated bentonite [18], Chitosan/kaolin/γ-Fe 2 O 3 [19], Chitosan-ball clay [20], Chitosan/Feldspar [21], Chitosan/rectorite [22] Oxalic Acid…”
Section: Literature Reviewmentioning
confidence: 99%